The CDK inhibitor p57(Kip2) enhances the activity of the transcriptional coactivator FHL2 - Kullmann, Michael Keith (Sci Rep, 2020)
The eukaryotic cell cycle is negatively regulated by cyclin-dependent kinase inhibitors (CKIs). p57(Kip2) is a member of the Cip/Kip family of CKIs and frequently inactivated by genomic mutations associated with human overgrowth disorders. There is increasing evidence for p57 to control cellular processes in addition to cell cycle and CDK regulation including transcription, apoptosis, migration or development. In order to obtain molecular insights to unknown functions of p57, we performed a protein interaction screen. We identified the transcription regulator four-and-a-half LIM-only protein 2 (FHL2) as a novel p57-binding protein. Co-immunoprecipitation and reporter gene assays were used to elucidate the physiological and functional relevance of p57/FHL2 interaction. We found in cancer cells that endogenous p57 and FHL2 are in a complex. We observed a substantial induction of established FHL2-regulated gene promoters by p57 in reporter gene experiments and detected strong induction of the intrinsic transactivation activity of FHL2. Treatment of cells with histone deacetylase (HDAC) inhibitors and binding of exogenous FHL2 to HDACs indicated repression of FHL2 transcription activity by HDACs. In the presence of the HDAC inhibitor sodium butyrate activation of FHL2 by p57 is abrogated suggesting that p57 shares a common pathway with HDAC inhibitors. p57 competes with HDACs for FHL2 binding which might partly explain the mechanism of FHL2 activation by p57. These results suggest a novel function of p57 in transcription regulation.